ENFORCEMENT OF JUSTICE IN INDIVIDUAL CRIMES RELATED TO THE DISTRIBUTION OF ILLEGAL CIGARETTES WITHOUT EXCISE TAX STAMPS - Agfanwarman, Muhammad; Nugroho, Taufiq (JCH (Jurnal Cendekia Hukum), 2025)
Cigarettes and tobacco products are a significant source of government revenue via the excise sector, and breaches of these regulations can adversely affect the state. This paper examines the implementation of legal penalties in combating the criminal offence of supplying illicit cigarettes without excise stamps, centring on the case of Vicky Utama Niriyanto. The defendant was convicted under Article 54 of Law No. 11 of 1995 regarding Excise, as amended by Law No. 39 of 2007, receiving a sentence of 10 months imprisonment and a fine of Rp50,000,000. The study's overarching goals are to suggest ways to improve judicial procedures and rules and to assess the efficiency with which law enforcement handles instances of illicit cigarette distribution. This study utilises a normative methodology with doctrinal analysis, scrutinising legislation, judicial rulings, and pertinent documents. The findings show that there are difficulties in enforcing the rules, even when criminal penalties for unlawful cigarette sales are consistent with those laws. This study helps to clarify the difficulties and potential solutions in implementing Indonesian legislation pertaining to the unlawful distribution of cigarettes. The results should also help lawmakers and lawyers better handle future instances like this one.